Effect of phospholipids on survival and molting synchronicity of mud crab larvae Scylla serrata were examined using Artemia enriched with five treatments of emulsion oil i.e. treatment with different level of soybean lecithin (SL) together with a level of DHA70G (referred to as DHA-SL0, 20 and 40) and treatment with SL and cuttle fish phospholipids (CPL) at 40 uL/L without DHA70G (referred to as WDHA-SL and WDHA-CPL). Survival rate, intermolt period, carapace width, and molting synchronicity wer - MUHAMMAD AGUS SUPRAYUDI; TOSHIO TAKEUCHI; KATSUYUKI HAMASAKI (Bogor Agricultural University, Indonesia, 2012)
Effect of phospholipids on survival and molting synchronicity of mud crab larvae Scylla serrata were examined using Artemia enriched with five treatments of emulsion oil i.e. treatment with different level of soybean lecithin (SL) together with a level of DHA70G (referred to as DHA-SL0, 20 and 40) and treatment with SL and cuttle fish phospholipids (CPL) at 40 uL/L without DHA70G (referred to as WDHA-SL and WDHA-CPL). Survival rate, intermolt period, carapace width, and molting synchronicity were evaluated. Additionally, lipid classes and fatty acid composition of enriched Artemia were analyzed. Survival rate, intermolt period, and carapace width at the first crab (FC) stage of mud crab larvae fed DHA-SL0 to 40 were similar to that of WDHA-CPL but higher than that of WDHA-SL (P < 0.05). Moreover, mud crab larvae fed DHA-SL20, DHA-SL40, and WDHA-CPL had a significantly higher molting synchronicity index compared to that of larvae fed WDHA-SL and DHA-SL0. It can be concluded that combination of phospholipids and essential fatty acids exhibited an additive effect in improving molting synchronicity of mud crab larvae.